INTRODUCTION OF COMPUTER DEVICES IN EARLY CHILDHOOD AT NAHDATUL ULAMA KINDERGARTEN PALEMBANG - Agustina, Sinta Bella (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
The introduction of computer devices in early childhood is a crucial issue in education in the digital era. The lack of access to appropriate methods for early childhood education is a challenge in applying technology in the educational environment. This study aims to identify effective computer device recognition methods for early childhood, analyze their level of understanding after being given learning, and examine the obstacles faced in their implementation. This study uses a qualitative approach with a descriptive method, where data is collected through observation, interviews with teachers and parents, and documentation of learning activities. The study results show that playing while learning with the active guidance of teachers can improve children's understanding of computer devices. However, the limited infrastructure and educators' readiness are still a challenge. Therefore, further support is needed to integrate technology into early childhood education.